Influence of CYP3A5 genetic variation on everolimus maintenance dosing after cardiac transplantation. (23rd November 2015) - Lesche, Dorothea; Sigurdardottir, Vilborg; Setoud, Raschid; Englberger, Lars; Fiedler, Georg M.; Largiadèr, Carlo R.; Mohacsi, Paul; Sistonen, Johanna
Abstract: Background: Everolimus (ERL) has become an alternative to calcineurin inhibitors (CNIs) due to its renal‐sparing properties, especially in heart transplant (HTx) recipients with kidney dysfunction. However, ERL dosing is challenging due to its narrow therapeutic window combined with high interindividual pharmacokinetic variability. Our aim was to evaluate the effect of clinical and genetic factors on ERL dosing in a pilot cohort of 37 HTx recipients. Methods: Variants in CYP3A5, CYP3A4, CYP2C8, POR, NR1I2, and ABCB1 were genotyped, and clinical data were retrieved from patient charts. Results: While ERL trough concentration ( C 0 ) was within the targeted range for most patients, over 30‐fold variability in the dose‐adjusted ERL C 0 was observed. Regression analysis revealed a significant effect of the non‐functional CYP3A5*3 variant on the dose‐adjusted ERL C 0 (p = 0.031). ERL dose requirement was 0.02 mg/kg/d higher in patients with CYP3A5*1/*3 genotype compared to patients with CYP3A5*3/*3 to reach the targeted C 0 (p = 0.041). ERL therapy substantially improved estimated glomerular filtration rate (28.6 ± 6.6 mL/min/1.73 m 2 ) in patients with baseline kidney dysfunction. Conclusion: Everolimus pharmacokinetics in HTx recipients is highly variable. Our preliminary data on patients on a CNI‐free therapy regimen suggest that CYP3A5 genetic variation may contribute to this variability.